Tetanus Neonatorum in the Bethesda Hospital Y ogyakarta - Marwoto Marwoto; Achmad Surjono (Indonesian Pediatric Society, 1976)
Thirty cases of tetanus neonatorum admitted to the Bethesda Hospital Yogyakarta, from January through December 1974, were analyzed. Twenty seven cases (90%) were born at home attended by traditional midwives, 2 (6.7%) were delivered at home attended by midwives while 1 (3.3%) was born in the obstetric ward of the hospital. The fatality rate is high. The possible cause of neonatal tetanus in these cases might be the delivery at home by traditional midwives and the application of contaminated materials such as traditional medicines on the umbilical stump. Tetanus neonatorum is an important cause of neonatal death in rural areas. The cost of treatment of tetanus neonatorum is much higher than the cost of antenatal tetanus immunization, which is one of the practical effective and safe methods in preventing tetanus neonatorum.